Investigation of senescence associated secretory phenotypes using MSD platform. (Eurasian Journal of Ecology, 2016)
This scientific research aimed to investigate senescence associated secretory phenotypes using up to date technologies. Furthermore, cell senescence stage was studied using senescence associated β – galactosidase (SA–β-gal) and 5-bromo-2'-deoxyuridine (BrdU) labelling index being used for cell proliferation analysis. Main senescence associated secretory phenotype components were determined using high throughput MSD (Mesoscale discovery) platform. Results obtained from this research have suggested that the MSD platform can be recommended as a reliable method for detecting senescence associated secretory phenotype components.
Keywords: cell senescence; secretory phenotype; fibroblasts; cytokines